Some Observations on BitTorrent Performance - Bharambe, Ashwin; Herley, Cormac; Padmanabhan, Venkat (Association for Computing Machinery, Inc., 2005)
In this paper, we present a simulation-based study of BitTorrent. Our results confirm that BitTorrent performs nearoptimally in terms of uplink bandwidth utilization and download time, except under certain extreme conditions. On fairness, however, our work shows that low bandwidth peers systematically download more than they upload to the network when high bandwidth peers are present. We find that the rate-based tit-for-tat policy is not effective in preventing unfairness. We show how simple changes to the tracker and a stricter, block-based tit-for-tat policy, greatly improves fairness, while maintaining high utilization.